Eotaxin-3 as a Plasma Biomarker for Mucosal Eosinophil Infiltration in Chronic Rhinosinusitis - Yamada, Takechiyo; Miyabe, Yui; Ueki, Shigeharu; Fujieda, Shigeharu; Tokunaga, Takahiro; Sakashita, Masafumi; Kato, Yukinori; Ninomiya, Takahiro; Kawasaki, Yohei; Suzuki, Shinsuke; Saito, Hidekazu (Frontiers in Immunology, 2019)
Objective: Chronic rhinosinusitis with nasal polyps exhibits marked eosinophilic infiltration and its mucosal eosinophilia is associated with more severe symptoms. The Japanese epidemiological survey of refractory eosinophilic chronic rhinosinusitis found that patients with nasal polyps required multiple surgeries when there were 70 or more infiltrating eosinophils / high-power field (HPF) in the mucosa. In order to identify plasma biomarkers for local eosinophil infiltration in rhinosinusitis for surgery, we examined the levels of molecules in the serum plasma of patients and compared the number of infiltrating eosinophils in the nasal mucosa. Materials and methods: Mucosal tissues from 97 patients with chronic rhinosinusitis (CRS) were obtained from the nasal polyps during surgery. Tissues were immediately fixed and sections were stained with hematoxylin-eosin. The number of eosinophils in the mucosa was counted at HPF (x 400). Blood samples were obtained and the plasma was stored at −80°C. We measured the plasma cytokine and chemokine levels using multiple assay systems according to the manufacturers’ protocols. The tissues were divided into high- and low-risk groups for recurrence after endoscopic sinus surgery (ESS). We also observed chemokine secretion from nasal fibroblasts. Results: The plasma level of eotaxin-3/ CC chemokine ligand 26 (CCL26) was significantly higher in the high-risk group for recurrence after surgery (p<0.005). The number of infiltrating eosinophils in the mucosa was significantly higher in the group with the higher eotaxin-3 level (p<0.001), but there was no significant difference in the blood eosinophil numbers among two groups. A significant positive correlation was found between the mucosal eosinophil count and the plasma levels of eotaxin-3 (p <0.005). The levels of interleukin 33 (IL-33) (p<0.001) and thymic stromal-derived lymphopoietin (TSLP) (p<0.005) werw were significantly higher in the group with the higher eotaxin-3 level. IL-13 strongly induced the secretion of eotaxin-3 from human nasal fibroblasts (p<0.05). Conclusion: This is the first report suggesting eotaxin-3 as a plasma biomarker for mucosal eosinophil infiltration. Fuerthermore, the level of eotaxin-3 was found to be closely related to IL-33 and TSLP levels which indicate respiratory diseases.